2014
DOI: 10.1155/2014/153712
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of Peptides by Calcium Ions: Investigation of a Calcium-Binding Motif

Abstract: We investigated calcium-binding motifs of peptides and their recognition of active functionalities for coordination. This investigation generates the fundamentals to design carrier material for calcium-bound peptide-peptide interactions. Interactions of different peptides with active calcium domains were investigated. Evaluation of selectivity was performed by electrospray ionization mass spectrometry by infusing solutions containing two different peptides (P1 and P2) in the presence of calcium ions. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…During the nano‐milling process, the fish bone collagens were degraded to peptides (Table ) which chelated calcium released form HAP through the formation of coordinate bonds and ionic bonds, increasing the solubility and stability of calcium ions (Vavrusova, Raitio, Orlien, & Skibsted, ). Jamalian et al () described multiple levels of calcium binding by peptide: (a) In the first level, the calcium ion and anions associated with glutamate and aspartate formed ionic coordination; (b) in the second level, the oxygen of hydroxy group (OH) as in threonine (T) or serine (S) provided a coordination site for binding; (c) in the third level, transfer of the OH proton from T and/or S to the neighboring amino group enhanced the coordination capacity of the peptide; and (d) in the fourth level, the amino acids asparagine (N) and tyrosine (Y) increased the potential binding sites which also favored the desired binding. Besides the formation of chelates, the exchange of calcium on the surface of HAP with the NH 3 + group of peptides might contribute to the release of ionic calcium (Bell & Mika, ).…”
Section: Resultsmentioning
confidence: 99%
“…During the nano‐milling process, the fish bone collagens were degraded to peptides (Table ) which chelated calcium released form HAP through the formation of coordinate bonds and ionic bonds, increasing the solubility and stability of calcium ions (Vavrusova, Raitio, Orlien, & Skibsted, ). Jamalian et al () described multiple levels of calcium binding by peptide: (a) In the first level, the calcium ion and anions associated with glutamate and aspartate formed ionic coordination; (b) in the second level, the oxygen of hydroxy group (OH) as in threonine (T) or serine (S) provided a coordination site for binding; (c) in the third level, transfer of the OH proton from T and/or S to the neighboring amino group enhanced the coordination capacity of the peptide; and (d) in the fourth level, the amino acids asparagine (N) and tyrosine (Y) increased the potential binding sites which also favored the desired binding. Besides the formation of chelates, the exchange of calcium on the surface of HAP with the NH 3 + group of peptides might contribute to the release of ionic calcium (Bell & Mika, ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrate that the addition of CEMP1-p3 to a constant composition seed growth solution promotes OCP crystal transformation into HA crystals. In this heterogeneous nucleation, CEMP1-p3 probably allowed a favorable thermodynamic state to overcome the energy barriers [17,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the multimeric association between peptides/proteins is due to the formation of ionic bonding between Ca 2+ ions and glutamate (E) and aspartate (D) residues or hydrogen bonding between hydroxyl groups (OH) of threonine (T) and/or serine (S) with the neighboring or asparagine (N) and tyrosine (Y) residues. Moreover, peptides/proteins with more number of asparagine (N) and tyrosine (Y) residues can help in increasing binding potential ( Jamalian et al, 2014 ). In horse gram, the stabilization of dimers is due to the electrostatic interaction between Lys-24 and Asp-75 = 76 residues of N- and C-terminal ends ( Kumar et al, 2004 ; Muricken and Gowda, 2010 ).…”
Section: Discussionmentioning
confidence: 99%